ALLOMETRIC GROWTH PATTERNS OF BODY AND CARCASS COMPONENT IN DOCKED AND INTACT KARADI LAMBS - D. A. O. Al-Sherwany,; J. E. Alkass, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
To study the allometric growth of body and carcass traits, twelve new born Karadi lambs were docked within 3 days of their birth using rubber-rings, and left with their mothers till weaning (2.5 months). Another 12 weaned Karadi lambs obtained from local market were left intact. Following an adaptation period of a week, the docked and intact lambs with an average initial weight of 16.83±1.522 and 19.92± 0.748kg, respectively were randomly divided into three equal groups to be slaughtered at 20, 30 and 40kg. Results revealed that the allometric growth coefficients of both docked and intact lambs of dissectible lean and bone were negative heterogenic (b